Model Propagasi tsunami Akibat Longsoran Gunung Anak Krakatau Besera Dampaknya Bagi Penduduk di Area Selat Sunda - Wiko Setyonegoro (LPPM Universitas Putera Batam, 2025)
Since 1883, the eruption of Mount Krakatoa in the Sunda Strait has generated destructive tsunamis. The most recent silent tsunami occurred on December 22, 2018, in Pandeglang Regency, Banten Province, killing 437 people. The source of this tsunami occurred suddenly and without any warning signs by the public. We suspect that the tsunami at Mount Anak Krakatau was a longsoran tebing Gunung Anak Krakataue phenomenon, where the side of the volcano collapsed directly into the surrounding seawater, triggering the propagation of tsunami waves. These waves propagated transversely following the ocean-bottom bathymetry structure around the tsunami source to the tsunami-affected area. This study used topographic and bathymetry data from FABDEM and BATNAS, respectively. The resulting landslide generated a tsunami with a height of 0.36–2.76 meters at 13 observation points, and was recorded as reaching a height of up to 27 meters on Rakata Island, located very close to Mount Anak Krakatau.